China's quest for foreign technology : beyond espionage - Hannas, Wm. C., 1946-; Tatlow, Didi Kirsten, 1967- (Milton Park, Abingdon, Oxon ; New York, NY: Routledge, 2021)
"This book analyzes China's foreign technology acquisition activity and how this has helped its rapid rise to superpower status. Since 1949, China has operated a vast and unique system of foreign technology spotting and transfer aimed at accelerating civilian and military development, reducing the cost of basic research, and shoring up its power domestically and abroad-without running the political risks borne by liberal societies as a basis for their creative developments. While discounted in some circles as derivative and consigned to perpetual catch-up mode, China's "hybrid" system of legal, illegal, and extralegal import of foreign technology, combined with its indigenous efforts, is, the authors believe, enormously effective and must be taken seriously. Accordingly, in this volume, 17 international specialists combine their scholarship to portray the system's structure and functioning in heretofore unseen detail, using primary Chinese sources to demonstrate the perniciousness of the problem in a manner not likely to be controverted. The book concludes with a series of recommendations culled from the authors' interactions with experts worldwide. This book will be of much interest to students of Chinese politics, US foreign policy, intelligence studies, science and technology studies, and International Relations in general"--
Part I. China's transfer venues -- Chinese technology transfer - an introduction -- Serve the motherland while working overseas -- China's talent programs -- Part II. The system in operation -- Foreign technology transfer through commerce -- The myth of the stateless global society -- Targeting defense technologies -- Part III. China's worldwide transfer networks -- Europe : a technology transfer mosaic -- Technology transfer from Germany -- Japan and South Korea -- Part IV. Case studies -- Sino-foreign research collaboration -- China's 'artificial' intelligence -- The impact of China's policies -- Part V. Technology in the shadows -- The People's Liberation Army and foreign technology -- Foreign technology and the surveillance state -- The United Front and technology transfer -- Part VI. Managing the transfer problem -- Chinese students, scholarship, and US innovation -- Economics espionage and trade secret theft cases in the US -- Mitigation efforts to date -- Conclusion -- Appendix : glossary of terms.
OCLC-licensed vendor bibliographic record.
Keywords: Technology and state -- China; Technology transfer -- China; Business intelligence -- China; POLITICAL SCIENCE / Political Freedom & Security / International Security; HISTORY / Asia / China; POLITICAL SCIENCE / Political Freedom & Security / Intelligence